In Vivo Deletion of Immunoglobulin Domains 5 and 6 in Neurofascin (Nfasc) Reveals Domain-Specific Requirements in Myelinated Axons - Thaxton, Courtney (Society for Neuroscience, 2010)
The formation of paranodal axo-glial junctions is critical for the rapid and efficient propagation of nerve impulses. Genetic ablation of genes encoding the critical paranodal proteins Caspr, contactin (Cont), and the myelinating glia-specific isoform of Neurofascin (Nfasc(NF155)) results in the disruption of the paranodal axo-glial junctions, loss of ion channel segregation, and impaired nerve conduction, but the mechanisms regulating their interactions remain elusive. Here, we report that loss of immunoglobulin (Ig) domains 5 and 6 in Nfasc(NF155) in mice phenocopies complete ablation of Nfasc(NF155). The mutant mice lack paranodal septate junctions, resulting in the diffusion of Caspr and Cont from the paranodes, and redistribution of the juxtaparanodal potassium channels toward the nodes. Although critical for Nfasc(NF155) function, we find that Ig5-6 are dispensable for nodal Nfasc(NF186) function. Moreover, in vitro binding assays using Ig5-6 deletion constructs reveal their importance for the association of Nfasc(NF155) with Cont. These findings provide the first molecular evidence demonstrating domain-specific requirements controlling the association of the paranodal tripartite complex in vivo. Our studies further emphasize that in vivo structure/function analysis is necessary to define the unique protein–protein interactions that differentially regulate the functions of Neurofascins during axonal domain organization.